Role of Share Ownership and Dividend Policy on Financial Performance (Case Study at Construction Service Company) - Yeni Sofiana; Hanum Elok Maghviro; Ananda Dwi Lestari (AIBPM Publisher, 2018)
The purpose of this study is to analyze financial performance seen on the basis of share ownership and dividend policy of the construction services company listed in Indonesia Stock Exchange (IDX) during 2014-2016. This study analyzes the role of share ownership and dividend policy of the construction services company and their impact on financial performance. Data of this research is Construction Company listed in Indonesia Stock Exchange which report Consolidated Financial Statements and audited in 2014-2016. The analytical technique used is Multiple Regression Analysis. The data of financial statements were downloaded from Indonesia Stock Exchange website and tested with SPSS 24 application. Result of this study is that the performance of Construction Company is influenced by Managerial Ownership positively and significantly affects all financial performance indicators, both Net Profit Margin, Return On Asset and Return On Equity, Institutional ownership has a negative and insignificant effect on financial performance indicator of Net Profit Margin and Return On Equity. While on Return On Asset has a positive effect but not significant. Dividend policy negatively affects all financial performance indicators. However, it is significant to Net Profit Margin and Return On Equity, while on Return On Asset, it is not significant. The findings of this study are financial performance of contruction companies that go public in Indonesia, is determined by the value of Managerial Ownership Financial Statement and ROE which will assist to provide useful information to other researchers, investors and banking companies